Finite Element Analysis of the Stiffness of a Kind of Double Helix Flexible Transmission Mechanism - Song Chengli; Zhu Xun; Lü Kunyong; Zhao Gaohui (Jixie chuandong)
The flexible transmission structure have more and more applications in minimally invasive surgical instrument. Due to the complexity of the structure,it is often difficult to calculate the mechanical property by the theoretical analysis of the structure. A double helix flexible transmission structure is proposed and the finite element model of the double helix structure is established in software ABAQUS and the influence of geometrical parameters on torsion stiffness of the double helix structure is analyzed,such as diameter,pitch,wall thickness and bottom radius. The results indicated that with the increase of nuclear diameter,pitch,thickness and bottom radius,the torsional stiffness increases,and with other parameters unchanged,the torsional stiffness and thickness are linear relationship,which has importance guiding significance for the design of the double helix structure.